2009
DOI: 10.1002/dvdy.21902
|View full text |Cite
|
Sign up to set email alerts
|

Novel markers of early ovarian pre‐granulosa cells are expressed in an Sry‐like pattern

Abstract: Mammalian gonad differentiation involves sexually dimorphic cell-fate decisions within the bipotential gonadal primordia. Testis differentiation is initiated by a center-to-poles wave of Sry expression that induces supporting cell precursors (SCPs) to become Sertoli rather than granulosa cells. The initiation of ovary differentiation is less well understood. We identified two novel SCP markers, 1700106J16Rik and Sprr2d, whose expression is ovary-biased during early gonad development, and altered in Wnt4, Sf1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…In the absence of Sry, as in XX genital ridges, ovary differentiation is initiated by the action of genes such as Bullejos and Koopman 2001;Wilhelm et al 2005). This expression pattern is also observed for some other genes expressed even earlier in both male and female embryos (Lee et al 2009), so it seems likely that the ''wave'' of Sry up-regulation depends on the appropriate combination of transcription factors being present in different parts of the gonad at different times. While it remains unclear how the center-to-pole expansion of Sry expression occurs, the result is that Sertoli cells do not differentiate synchronously in all parts of the gonad, a situation that has consequences for the formation of ovotestes in some situations, as discussed below.…”
Section: Specification Of Pre-sertoli Cellsmentioning
confidence: 98%
“…In the absence of Sry, as in XX genital ridges, ovary differentiation is initiated by the action of genes such as Bullejos and Koopman 2001;Wilhelm et al 2005). This expression pattern is also observed for some other genes expressed even earlier in both male and female embryos (Lee et al 2009), so it seems likely that the ''wave'' of Sry up-regulation depends on the appropriate combination of transcription factors being present in different parts of the gonad at different times. While it remains unclear how the center-to-pole expansion of Sry expression occurs, the result is that Sertoli cells do not differentiate synchronously in all parts of the gonad, a situation that has consequences for the formation of ovotestes in some situations, as discussed below.…”
Section: Specification Of Pre-sertoli Cellsmentioning
confidence: 98%
“…Kim et al [43] examined expression of Pld1/PLD1 in various mouse tissues and demonstrated PLD1 localization to granulosa cells of growing follicles, suggesting a role in regulation of follicular growth. Sprrd2 belongs to the small proline-rich gene family encoding a structural protein associated with the formation of protective barriers provided by stratified squamous epithelium [46], and recently was demonstrated to exhibit a center-to-pole expression pattern during fetal ovarian development [47]. Expression of Pld1 and Sprrd2 during the earliest stages of fetal ovarian development is a new finding and suggests that both genes are important novel regulators of pre-granulosa cell development.…”
Section: Expression Pattern Of Identified Genes By Real-time Pcr and mentioning
confidence: 99%
“…1I). Moreover, some of these cells appeared to be positive for SPRR2d, another early pre-granulosa cell marker (Lee et al, 2009;Bouma et al, 2010) (supplementary material Fig. S2B).…”
Section: Two Populations Of Ovarian Somatic Cells Retain Sdsi In Fetamentioning
confidence: 99%